G protein-coupled estrogen receptor correlates with Dkk2 expression and has prognostic impact in ovarian cancer patients - Fraungruber, Patricia; Kaltofen, Till Rolf Hans; Heublein, Sabine; Kuhn, Christina; Mayr, Doris; Burges, Alexander; Mahner, Sven; Rathert, Philipp; Jeschke, Udo; Trillsch, Fabian (Frontiers in endocrinology, 2021)
Purpose: Wnt pathway modulator Dickkopf 2 (Dkk2) and signaling of the G-protein coupled estrogen receptor (GPER) seem to have essential functions in numerous cancer types. For epithelial ovarian cancer (EOC), it has not been proven if either Dkk2 or the GPER on its own have an independent impact on overall survival (OS). So far, the correlation of both factors and their clinical significance has not systematically been investigated before. Methods: Expression levels of Dkk2 were immunohistochemically analyzed in 156 patient samples from different histologic subtypes of EOC applying the immune-reactivity score (IRS). Expression analyses were correlated with clinical and pathological parameters to assess for prognostic relevance. Data analysis was performed using Spearman’s correlations, Kruskal-Wallis-test and Kaplan-Meier estimates. Results: Highest Dkk2 expression of all subtypes was observed in clear cell carcinoma. In addition, Dkk2 expression differed significantly (p4) and GPER (IRS>8), had a significantly better overall survival compared to patients with low expression (61 vs. 33 months; p=0.024). Conclusion: Dkk2 and GPER expression correlates in EOC and combined expression of both is associated with improved OS. These findings underline the clinical significance of both pathways and indicate a possible prognostic impact as well as a potential for treatment strategies addressing interactions between estrogen and Wnt signaling in ovarian cancer.